2003
DOI: 10.1074/jbc.m209673200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Proliferation of Rat Hepatic Stellate Cells by Galectin-1 and Galectin-3 through Different Intracellular Signaling Pathways

Abstract: We found that the expression of galectin-1 and galectin-3 was significantly up-regulated in hepatic stellate cells (HSCs) both in the course of their transdifferentiation into myofibroblasts, a process of "self-activation," and in the fibrosis of liver tissues. Recombinant galectin-1 and galectin-3 stimulated the proliferation of cultured HSCs via the MEK1/2-ERK1/2 signaling pathway. However, galectin-3 utilized protein kinases C and A to induce this process, whereas galectin-1 did not. We also found that thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 70 publications
6
99
0
Order By: Relevance
“…Galectin 1/3 are members of the family of β-galactosidebinding animal lectins (25) and play a role in a variety of cell functions, including proliferation, migration and adhesion characteristics (26,27). In this study, the expression of galectin 1/3 was observed at lower frequencies than the remaining three proteins in the epithelial and stromal cells in AHs, whereas it was strongly expressed in epithelial and stromal cells, respectively, in ACs.…”
Section: Discussionmentioning
confidence: 65%
“…Galectin 1/3 are members of the family of β-galactosidebinding animal lectins (25) and play a role in a variety of cell functions, including proliferation, migration and adhesion characteristics (26,27). In this study, the expression of galectin 1/3 was observed at lower frequencies than the remaining three proteins in the epithelial and stromal cells in AHs, whereas it was strongly expressed in epithelial and stromal cells, respectively, in ACs.…”
Section: Discussionmentioning
confidence: 65%
“…20 Other studies have shown that galectin-3 expressed by liver analogues of macrophages (ie, Kupffer cells) induce the synthesis of excess fibril-forming collagens in liver. 21 Earlier studies have demonstrated the relation between galectin-3 expression and the cell cycle. Nuclear galectin-3 expression is associated with cell proliferation, and this effect is mediated through enhanced cyclin D1 promoter activity.…”
Section: Galectin-3 Structure Functions and Relevance For Cardiac Rmentioning
confidence: 99%
“…Maeda et al showed that galectin-3 induced hepatic stellate cells transdifferentiation into myofibroblasts via the mitogenactivated protein kinase/extracellular signal-regulated kinase (ERK)-ERK 1/2 signaling pathway and, at variance with galectin-1, in a protein kinase C-and A-dependent manner [53], whereas MacKinnon et al showed that galectin-3 ablation reduced alveolar epithelial cell EMT in response to TGF-β1 [50]. In addition, galectin-3 plays a complex role in the modulation of immune/inflammatory function, with distinct pro-inflammatory actions, but also with relevant anti-inflammatory effects which predominate under chronic conditions [7].…”
Section: Galectin-3 As a Disease Mediator: Animal Studiesmentioning
confidence: 99%